Pricing liquidity support: A PLB for Switzerland - Cyril Monnet; Dirk Niepelt; Remo Taudien (University of Bern, Department of Economics, 2025)
The proposed revision of the Swiss Banking Act introduces a public liquidity backstop (PLB) for distressed systemically important banks (SIBs), in part to facilitate resolution. We examine the impact of the PLB on fiscal balances, societal welfare, and the incentives of bank shareholders and management. A PLB, like toobig-to-fail (TBTF) status, acts as a subsidy for non-convertible bonds, which can create negative externalities. Corrective measures must be implemented before the PLB is activated to align incentives with societal interests. We conservatively estimate that Swiss SIBs' TBTF status results in funding cost reductions far greater than the proposed ex-ante compensation, with UBS Group AG alone gaining at least USD 2.9 billion in 2022. The risk for Switzerland of hosting SIBs warrants additional precautionary savings.
Keywords: 330; Bankrecht; Bankenliquidität; Bankinsolvenz; Bürgschaft; Systemrisiko; Schweiz